2012
DOI: 10.1007/978-3-642-32512-0_40
|View full text |Cite
|
Sign up to set email alerts
|

On the Coin Weighing Problem with the Presence of Noise

Abstract: Abstract. In this paper we consider the following coin weighing problem: Given n coins for which some of them are counterfeit with the same weight. The problem is: given the weights of the counterfeit coin and the authentic coin, detect the counterfeit coins a with minimal number of weighings. This problem has many applications in computational learning theory, compressed sensing and multiple access adder channels.An old optimal non-adaptive polynomial time algorithm of Lindstrom can detect the counterfeit coi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The class r-LF is studied in [37,78,79,113,145,200,204,264,266]. It is shown that OPT AD (r-LF) = OPT NAD (r-LF) = Θ r log(n/r) log r .…”
Section: Classes Of Arithmetic Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…The class r-LF is studied in [37,78,79,113,145,200,204,264,266]. It is shown that OPT AD (r-LF) = OPT NAD (r-LF) = Θ r log(n/r) log r .…”
Section: Classes Of Arithmetic Functionsmentioning
confidence: 99%
“…Note here that in the literature they use log(n/r) to mean log(2n/r). In [37], Bshouty shows that it is optimally adaptively learnable. The problem is still open for the non-adaptive learning.…”
Section: Classes Of Arithmetic Functionsmentioning
confidence: 99%
See 3 more Smart Citations